Participatory Politics, Social Cooperation, and Economic Stability - Rodrik, Dani (American Economic Review, 2000)
Few would doubt the proposition that political institutions matter for economic development. Yet we lack robust generalizations and systematic evidence on how exactly they do so. In this short paper, I draw attention to a regularity in the cross-national data that has received little attention to date: participatory political regimes are associated with significantly lower levels of aggregate economic instability. After presenting some of the evidence in the next section, I speculate that the reason has to do with the propensity of democracy to moderate social conflict and induce compromise. I discuss three distinct arguments as to why this may be the case. I. Some evidence The relationship between democracy and economic growth has been studied extensively. The data tend to show that democracy has no systematic effect on long-run growth rates. The top panel of Figure 1 shows a typical result: the partial correlation between an index of democracy during the 1970s and subsequent economic growth is virtually zero. The relationship between democracy and volatility in economic performance, on the other hand, is negative, statistically significant, and quantitatively large. This is shown in the bottom panel of Figure 1: